Análise do desempenho da virtualização leve para ambientes com Edge Computing baseada em NFV - Trindade, Leon Valentim Porto (2018)
The Network Function Virtualization (NFV) paradigm is changing the way network services are provided, allowing the same degree of versatility and agility as ever seen in cloud computing. In fact, NFV proposes to change the network functions that are currently performed in the so-called middleboxes, a dedicated hardware, in virtual functions. That is, turn closed solutions into simple software images, called Virtual Network Function (VNF), which can be consolidated and run on industry standard servers. However, it is possible to implement as virtual functions through traditional virtualization in hypervisors or in lightweight virtualization, constituting a compromise between flexibility and performance. Thus, this work compares the performance in environments that use virtualization technology with hypervisor to those that uses a container, for the purpose of verify the best for operational environments allied to the concept of Edge Computing in NFV. However, it is intended to gauge the ability for the technologies to be transparent to the user regarding performance. In order to do so, comparisons of CPU, memory, disk I/O, network and application were made, evidencing a low overhead of lightweight virtualization that comes close to the native scenario in certain cases.